An upstream enhancer regulating brown-fat-specific expression of the mitochondrial uncoupling protein gene. - Kozak, U C (1994)
Previous studies on the regulation of a Ucp minigene in transgenic mice demonstrated that the sequences necessary for brown-fat-specific expression and inducibility by norepinephrine were located in the 5' flanking region between 1 and 2.8 kb from the transcriptional start site. We have investigated this region in more detail in cultured mouse brown adipocyte tumor cells. Deletion analysis of two types of chloramphenicol acetyltransferase reporter gene constructs under control of either the Ucp promoter or a heterologous herpes simplex virus-tk promoter defined an enhancer in a 220-bp HindIII-XbaI fragment which was essential for both brown fat specificity and norepinephrine inducibility. Site-directed mutagenesis of the reporter gene constructs established that independent mutations to a cyclic AMP-responsive element (CRE-2) or one of two TTCC motifs (BRE [brown fat regulatory element]), all within 17 bp, eliminated transient expression. Competitive DNA mobility shift assays with probes of the CRE and BRE motifs indicate that nuclear proteins interact with these motifs in a cooperative, synergistic manner. While these CRE-BRE probes do not show changes in binding which is dependent on norepinephrine treatment, a probe containing a third TTCC motif located 130 bp downstream of BRE-1 does show this dependency. The results indicate that a complex interaction of the CRE and BRE motifs, which cannot be functionally separated, control Ucp expression.